Bandilune
6 год назад
Решите уравнение:(х-2)³-3х²-4 = (х-3)³
ОТВЕТЫ
Evdokim
Jun 30, 2019
Раскрываем скобки
x^3 - 3*2x^2 + 3*4x - 8 - 3x^2 - 4 = x^3 - 3*3x^2 + 3*9x - 27
x^3 благополучно сокращается.
-6x^2 + 12x - 8 - 3x^2 - 4 = -9x^2 + 27x - 27
x^2 тоже сокращается, остается линейное уравнение.
27x - 12x = 27 - 12
15x = 15
x = 1
x^3 - 3*2x^2 + 3*4x - 8 - 3x^2 - 4 = x^3 - 3*3x^2 + 3*9x - 27
x^3 благополучно сокращается.
-6x^2 + 12x - 8 - 3x^2 - 4 = -9x^2 + 27x - 27
x^2 тоже сокращается, остается линейное уравнение.
27x - 12x = 27 - 12
15x = 15
x = 1
282